POLITIK DAN BIROKRASI: Reposisi Peran Birokrasi Publik dalam Proses Politik Lokal - Alamsyah Alamsyah (Jurnal Administrasi Publik, 2003)
Based on assumption that is politics and administration does not differents, this paper will be analyzed interrelation between politics and bureaucracy. This is a classical themes in public administration. But, after Indonesian government carrying out decentralization policy under UU No. 22 Tahun 1999, it is very interesting to elaborate this themes. Why? Because of decentralization policy have several impact to local political process. For example, legislative institution have more power than before. In this case, we can say that - in the hypothetic manner - legislative institution (as a real manifestation of politics) tend to donimated decision making process. For bureaucracy, it is not a good news. Under New Order regime, bureaucracy institution was very stronger than legislative institution. According to this change, this paper will be examined what it's the meaning of this change, especially when we search for the better understanding on politic-bureaucracy nexus. This paper will be focuse on three questions: (1) what is the implication of these change to bureaucratic reform of local government; what is the imperative process for bureaucratic government reform; (2) deal with to justice values, how to carrying out these reform?